2011
DOI: 10.1111/j.1447-0756.2010.01348.x
|View full text |Cite
|
Sign up to set email alerts
|

Minilaparotomy hysterectomy: A worthwhile alternative

Abstract: Minilaparotomy hysterectomy through ≤5 cm Pfannenstiel incision provides an appealing, effective, expeditious, minimal access and less invasive cost-effective option/alternative to the traditional abdominal approach obviating the need for any additional expensive equipment and, above all, improves upon the perioperative outcome, notwithstanding, whatsoever, on the quality of surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
4
3
1
Order By: Relevance
“…These results are similar to that reported by Sharma et al (7) and Mahendru et al (13) . This significant difference could be attributed to less intestinal handling ,less exposure to room temperature with consequent tissue dryness ,non use of laparotomy pads ,and less electrolyte disturbance.…”
Section: Comparative Study Between Minilaparotomy ………supporting
confidence: 83%
See 3 more Smart Citations
“…These results are similar to that reported by Sharma et al (7) and Mahendru et al (13) . This significant difference could be attributed to less intestinal handling ,less exposure to room temperature with consequent tissue dryness ,non use of laparotomy pads ,and less electrolyte disturbance.…”
Section: Comparative Study Between Minilaparotomy ………supporting
confidence: 83%
“…Also, the mean pain score was higher (5.2 ± 1.1) and sometimes the patients needed further analgesia . These results are comparable to that reported by Sharma et al (7) and Mahendru et al (13) . Regarding group B ,all the parameters of comparison were superior to that in group A .The recent trends towards minimally invasive surgery has lead to the continuous trials of refinement in laparotomy techniques .…”
Section: Comparative Study Between Minilaparotomy ………supporting
confidence: 82%
See 2 more Smart Citations
“…Studies conducted to compare the results of conventional abdominal hysterectomy and MLH concluded that MLH provides a minimal access and less invasive cost-effective option/alternative to the traditional abdominal approach obviating the need for any additional expensive equipment and, above all, improves upon the perioperative outcome, notwithstanding, whatsoever, on the quality of surgery [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%